2011
DOI: 10.2355/isijinternational.51.169
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Martensite Volume Fraction in Fe–Cr–Ni Alloys

Abstract: Martensitic stainless steels, such as those in the AISI type 4xx series, have good corrosion resistance, good edge retention, high strength, high hardness, and good wear resistance. 1) Maintaining control over the amount of martensite is important when designing alloy compositions and determining heat treatment conditions, because of the contribution of martensite to the mechanical and electrochemical properties in these stainless steels. Dilatometric analysis has been widely used for determining quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The X-ray diffraction results can also be applied to estimate the carbon content (wt%) in the retained austenite [23,24] :…”
Section: Methodsmentioning
confidence: 99%
“…The X-ray diffraction results can also be applied to estimate the carbon content (wt%) in the retained austenite [23,24] :…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [ 13 , 14 ] suggested a dilatometric analysis model for the isothermal austenite decomposition in both hyper-eutectoid and hypo-eutectoid Fe–C steels. Some researchers took the effect of alloying elements on lattice parameters into account [ 15 , 16 ]. Garcia et al [ 17 ] and Kop et al [ 1 ] improved the model to analyze the transformations in continuously heating or cooling steels.…”
Section: Introductionmentioning
confidence: 99%